Politik Hukum Pemulihan Ekonomi Nasional Akibat Pandemi Covid-19 Perspektif Konstitusi Ekonomi - Lutfi, Mustafa; Supriyadi, Aditya Prastian (Fakultas Syariah, 2021)
Abstract :The Covid-19 pandemic has slowed the pace of economic growth in Indonesia. As a result, several business sectors in the community experienced a decline, so the state issued a legal policy to take steps to resolve it. Legal politics as a form of government policy in an effort to restore the national economy is a necessity. This article uses a type of normative juridical research method, with a statutory and conceptual approach, legal materials (primary, secondary, tertiary) are analyzed using the content analysis method. This article shows and emphasizes the urgency of the government's legal politics in efforts to recover the national economy due to the Covid-19 pandemic. In the process of its formation, it certainly requires a comprehensive, integrated and targeted policy set. The 1945 Constitution Article 22 paragraphs (1-3) provides space for the government to stipulate Perpu No. 1 of 2020 becomes Law No. 2 of 2020 as a legal umbrella in an effort to maintain the resilience of all elements of the nation from all threats that endanger the safety of the people of the nation and state. The role of the government's legal policy in national economic recovery has a central position in anticipating a fragile